Neoplatonizm i chrześcijaństwo w twórczości Synezjusza z Cyreny (370–414) – przyczynek do zagadnienia - Kroczak, Justyna (Studia z Historii Filozofii, 2024)
The article presents creative personality of Synesius of Cyrene (4th/5th century CE) against the background of ideological tendences of late antiquity. It aims to answer two questions: First, whether the term Christian Neoplatonism, rightly criticized in relation to patristic writers, reflect the nature of Synesius' outlook, and second, whether his work significantly complements our image of late antiquity in its philosophical aspect, viewed as a clash between Christian and classical, mainly Neoplatonic, philosophic paradigms. Synesius’ rich correspondence, consisting of one hundred and fifty-six letters, provides the main source for the present analysis; yet, his other works (mainly the Hymns) and biographical details are also drawn upon to attain a wholistic perspective. This broader selection of sources is necessary because a reading of his works leaves some doubt as to his ideological affiliation. On the one hand, he was a disciple of Hypatia, and, on the other, a friend of St. Theophi lus of Alexandria, who called him to the post of bishop. These and other ambiguities in the life and outlook of Synesius make him an interesting object of analysis.